Immune Response to Chlamydial 60-Kilodalton Heat Shock Protein in Tears from Nepali Trachoma Patients - Hessel, Tracey (American Society for Microbiology, 2001)
Although the host immune response to the 60-kDa chlamydial heat shock protein (hsp60) has been implicated in trachoma pathogenesis, no studies have examined mucosal immune responses to hsp60 in populations for which chlamydia is endemic. Tears and sera from Nepali villagers were reacted against hsp60 fusion proteins, whole hsp60, and the major outer membrane protein (MOMP). Tears from villagers without disease were anti-hsp60 immunoglobulin G (IgG) reactive in 6 (38%) of 16 villagers compared with 36 (90%) of 40 with follicular trachoma (TF) (P < 0.001); 47 (89%) of 53 with inflammatory trachoma (TI) (P < 0.001); and 31 (84%) of 37 with conjunctival scarring (TS) (P = 0.002). By multivariate analysis, odds ratios for tear hsp60 IgG immunoreactivity in villagers with TF, TI, and TS were 49.2 (confidence interval [CI], 2.7 to 898), 22.6 (CI, 3 to 170), and 13.6 (CI, 1.4 to 133), respectively. There were no significant differences for tear IgA or secretory IgA (sIgA) reactivity to hsp60 or for tear sIgA and IgG reactivity to MOMP. Serum anti-hsp60 IgG immunoreactivity was associated with TI only. These data suggest that anti-hsp60 IgG immunoreactivity represents largely locally derived antibodies, which may promote disease pathology. In contrast, nonspecific high rates of anti-hsp60 sIgA antibodies suggest chronic or repeat stimulation from an endemic source of organisms.